TEORI STRUKTURASI DALAM KEPEMIMPINAN LOKAL - WA, Priyandono (Transformasi, 2011)
Abstract Structuring of local leadership is a term that saw the potential in a direction that can be initiated by the institutionalization of the quality of local governments with existing regional leaders, including district heads, mayors and community leaders. Awareness to develop the quality and awareness of social structure for developing human resources as a whole will produce a synergy of quality of government as well. To that end, this expectation rests on the embryonic stage Regents and Mayors Â  Key word : local leadership, Structuration